Building Patient Satisfaction based on the Quality of Health Services based on The Digital-Based Patient's Experience at the Dental and Oral Health Service Facility in West Java - Julia Famor Pratami; Ratih Hurriyati; Puspo Dewi Dirgantari (Budapest International Research and Critics University, 2021)
The health care industry in Indonesia continues to grow, but the health industry has a low level of resilience. This study aims to elaborate the relationship between digital patient experience, innovation, and patient satisfaction at dental health care facilities and in West Java. Data collection was carried out using a survey of 100 patients spread across West Java. Then, the data were analyzed using path analysis and regression. The results of the study reveal that there is an indirect effect between digital patient experience and patient satisfaction through innovation. Meanwhile, digital patient experience does not directly affect patient satisfaction. Novelty is obtained by testing and analyzing the relationship between innovation, digital patient experience, patient satisfaction in one model, as well as the use of health care facilities in West Java as a unit of research analysis.